CRIMINAL LAW ENFORCEMENT OF BRAND RIGHTS IN THE INDUSTRY ERA 4.0 - Yana Indawati (Universitas Surakarta, 2020)
The purpose this study is to identify element of error in trademark infringement based on the Trademark and Geographical Indication Law and the Criminal Law enforcement for trademark infringement based on the Trademark and Geographical Indication Law. In this study, the authors conducted normative legal research. Where in this study using the normative Juridical approach, namely research conducted by examining library materials or secondary data. Research materials used are secondary data, namely data obtained from official documents, books related to the object of research, research results in the form of reports, theses, dissertations and statutory regulations. The result indicated that first, the elements of error in the violation of marks in the Trademark Law and Geographical Indications are seen in the actus reus and mens rea perpetrators of trademark infringement. Where actus reus is manifested as an evil act that is deliberately committed, and mens rea is manifested in the form of evil intent, namely using it without rights. Second, enforcement of criminal law for violation of marks based on the Trademark and Geographical Indication Law is manifested in the imposition of criminal sanctions as stipulated in the provisions of Article 100 and Article 101 of the Trademark and Geographical Indication Law. Where in addition to the form of criminal sanctions there are also fines. Keywords: Industry 4.0, law enforcement, trademark, geographical indication.